Linguistic Economy in Urban Arabic: A Sociolinguistic Study of Naḥt in Egyptian Colloquial Arabic - Mufrodi; Zaki Ghufron; Hannanah Mukhtar; Azizah Alawiyyah; Yuttana Kuakul (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study investigates the productivity and structural patterns of naḥt (morphological acronyms) in Egyptian Arabic ('āmiyah), aiming to explain how these forms function as mechanisms of linguistic economy and socio-cultural adaptation in urban speech communities. Departing from earlier scholarship that primarily examines naḥt in Fusḥā and classical religious contexts, this research focuses on spoken dialectal data that remain under-documented in morphological studies. Using a qualitative design with linguistic content analysis, the study analyzes a corpus of Egyptian 'āmiyah drawn from films, social media discourse, and semi-structured interviews with native speakers. The findings demonstrate that dialectal naḥt forms -such as ma'lish, 'ashān, fīn, and away- emerge through systematic processes of phonological contraction, segmental elision, and morphological reanalysis. These forms are not random reductions but rather patterned innovations shaped by communicative efficiency, frequency of use, and urban interactional norms. The study concludes that naḥt in Egyptian Arabic represents a productive morphological strategy that reflects both structural simplification and socio-pragmatic negotiation in informal contexts. By foregrounding spoken data, this research contributes to expanding Arabic morphological theory beyond Fusḥā-centric models and provides pedagogical implications for teaching Arabic as a foreign language within context-sensitive and dialect-aware frameworks.